Genome-Wide Analysis of Circular RNAs Mediated ceRNA Regulation in Porcine Embryonic Muscle Development - Hong, Linjun; Gu, Ting; He, Yanjuan; Zhou, Chen; Hu, Qun; Wang, Xingwang; Zheng, Enqin; Huang, Sixiu; Xu, Zheng; Yang, Jie; Yang, Huaqiang; Li, Zicong; et al. (Frontiers in Cell and Developmental Biology, 2019)
Many circular RNAs (circRNAs) have been discovered in various tissues and cell types in pig. However, the temporal expression pattern of circRNAs during porcine embryonic muscle development remains unclear. Here, we present a panorama view of circRNA expression in embryonic muscle development at 33-, 65- and 90-days post-coitus (dpc) from Duroc pigs. An unbiased analysis reveals that more than 5000 circRNAs specifically express in embryonic muscle development. The amount and complexity of circRNA expression is most pronounced in skeletal muscle at day 33 of gestation. Our circRNAs annotation analyses show that “hot-spot” genes produce multiple circRNA isoforms and RNA binding protein (RBPs) may regulate the biogenesis of circRNAs. Furthermore, we observed that host genes of differentially expressed circRNA across porcine muscle development are enriched in skeletal muscle function. A ceRNA network analysis of circRNAs reveals that circRNAs regulate muscle gene expression by functioning as miRNA sponges. Finally, our experimental validation demonstrated that circTUT7 regulate the expression of HMG20B in a competing endogenous RNA (ceRNA) mechanism. Our analyses show that circRNAs are dynamically expressed and interacting with muscle genes through ceRNA manner, suggesting their critical functions in embryonic skeletal muscle development.